PMO-017 Perinatal hepatitis B in a high prevalence inner city population: direct electronic referral improves care. (28th May 2012) - Matthews, H C; McLeod, M A; Oakes, K; McCurdy, G; Zuckerman, M; Carey, I; Harrison, P; Agarwal, K
Abstract : Introduction: There is little work evaluating perinatal Hepatitis B (HBV) care despite extensive recent guidelines from several sources. Seamless interaction between maternity and specialist clinical services is key to improvement of screening, education and patient care in HBV. We introduced a new electronic patient referral system (EPR) from Midwifery Services to Hepatology. We reviewed care provision and investigated the impact of EPR. Methods: Data were collected from the Kings College Hospital (KCH) Maternity Services Record and Liver Services Database for 6 months before and 6 months after introduction of EPR. Results: The burden of HBV in our patient group is high. Of 6796 women attending antenatal booking during the study, 101 tested positive for HBV exposure (1.5%). Liver services received referrals from Maternity for 84 women during the two time periods. Four women (4.8%) were HBsAg negative, HBcAb positive. The majority of patients were Black African (61%) followed by Chinese (23%) then Eastern European (8%). 66% had no previous Hepatology contact and represent new diagnoses. 11.4% tested eAg positive (n=9) of whom only two had HBV DNA checked antenatally and were started on Tenofovir therapy due to viral loads >10 6 IU/ml. Two HBeAg +ve patients attended booking too late to be eligible. Neonatal active and/or passive immunisation was recommended appropriately in all cases. Referral rates for eligible patients doubled following introduction of EPR. In the initial 6 months 32% of patients testing HBsAg positive at Maternity Services were referred to Hepatology (n=16) compared to 63% (n=33) following introduction of EPR. Mean gestation at referral improved from delivery date +2 weeks compared to 27 weeks gestation. Measurement of antenatal HBV DNA improved from 33% of patients referred to 81%. No HBeAg negative patient who had HBV DNA analysis had a viral load >10 4 IU/ml. No patient had HBV DNA rechecked during pregnancy. Conclusion: Maternal seroprevalence in our population is high with most patients being new HBV diagnoses. An individualised liaison pathway for antenatal woman has improved service by: Doubling referral rates to specialist services Increasing potential access to third trimester Tenofovir if required Increasing HBV DNA analysis rates without duplication of HBV DNA testing To optimise preventative public health approaches to HBV wider use of this referral model should be considered in high prevalence settings. Education of the community and other health providers remains critical. Competing interests: None declared. References: 1. Stein HJ, Sendler A, Fink U, et al. Multidisciplinary approach to esophageal and gastric cancer. Surg Clin North Am 2000;80 :659–86. 2. Weimann A, Braga M, Harsanyi L, et al. European society of parenteral and enteral nutrition guidelines on enteral nutrition: Surgery including organ transplantation. Clin Nutr 2006;25 :224–44. 3. Scottish Intercollegiate Guidelines . Sign 87 Management of Oesophageal and Gastric Cancer: A National Clinical Guideline . Quality Improvement Scotland, 1996.